Evaluasi Dan Rekomendasi Perbaikan Website PT. Fokus Solusi Utama Dengan Menggunakan Metode Usability Testing Dan Heuristic Evaluation - Ayu Pratiwi; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Fokus Solusi Utama is a company engaged in information technology that uses the website as a marketing medium. Based on observations and pre-research interview results there are shortcomings of the website, including content structuring problems, inconsistencies between content, image size, and others. Excavation of the problem is also done to the web design, where the company needs an improvement of the website in terms of appearance. This research aims to evaluate the current website as well as provide improvement recommendations to improve the company's branding. The methods used are usability testing and heuristic evaluation. The usability testing method was conducted on 5 respondents based on work background and age. The heuristic evaluation method is done to 4 expert level double and 1 expert level regular, the results obtained from this study are complete because it is obtained from experts and users. Based on the evaluation results, the problems found were 62 problems. The improvement recommendations follow U.S. Department of Health and Human Services (HHS) guidelines and expert solutions, after prioritizing recommendations produced 33 recommendations using prototypes and 10 functionality recommendations, a much-changed section that is website navigation and home page. After the improvement recommendations are given, a final test is conducted to compare the value before and after the evaluation, the results obtained are the learnability, efficiency, and satisfaction components have improved, and the error component has decreased.